Planning the structure of SGE debt as an opportunity for local development - Dylewski, Marek (Planowanie struktury zadłużenia JST szansą na stabilny rozwój lokalny, 2015)
Projects and programmes realized in the public sector, including self-government entities, are supposed, above all, to satisfy the needs of the society. From the perspective of self-government entity the objective of the task is a given local or regional community. The vast majority of projects and programmes are realized with the use of debt instruments. Self-government public debt is subject to limitation; therefore, it is important not only to comply with the legally binding limits in terms of incurred debt but also to plan the structure of self-government public debt together with the instalments due for payment in a given period and together with the buyout of debt instruments. The purpose of the following paper is to present the significance of the planning approach in creating stable and balanced local development in the perspective of empirical study, and the current approach towards debt planning by self-government entities (SGE)
Biblioteka Regionalisty, 2015, Nr 15, s. 7-18
Keywords: finance; self-government finances; debt; planning; local development; finanse; finanse samorządu terytorialnego; dług; planowanie; rozwój lokalny